Implementation of Character Education Based on Anti-Corruption Values Through Extracurricular and Habituation in Elementary School - Sari, Vina Kurnia; Akhwani, Akhwani (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The era of globalization that is increasingly developing seems to have eroded the morale of the nation’s children. Moral degradation which becomes a scourge from year to year is the occurrence of corruption. Character education based on anti-corruption values needs to be implemented from an early age starting from the elementary school level. This study aims to analyze the implementation of character education based on anti-corruption values through extracurricular activities and habituation. The research is based on the literature study process. The type of research used is descriptive qualitative analysis, where it emphasizes the ability to analyze and examine the literature sources that have been obtained. The results of this study indicate that the implementation of anti-corruption values through extracurricular learning is carried out by instilling the values of honesty, independence, discipline, responsibility, courage, care, and justice that can be realized through activities such as scouting. Providing strengthening of faith or increasing the religious side can be realized through memorizing short letters in juz 'amma, as well as praying dhuha. Meanwhile, the implementation of anti-corruption values through habituation can be realized through the application of an honest canteen, pocketbooks, caring for the environment, social care, and accustoming students to not cheating.